Antennal Lobe Atlas of an Emerging Corn Pest, Athetis dissimilis - Dong, Jun-Feng; Jiang, Nan-Ji; Zhao, Xin-Cheng; Tang, Rui (Frontiers in Neuroanatomy, 2020)
Moths develop sophisticated olfactory systems to sense the airborne chemical cues from the environment. Understanding the structural basis in the neuronal center is a fundamental neuroethological step. Little is known about the emerging crop pest Athetis dissimilis with regard to its morphology or its neuronal organizations. Through antibody staining and digital 3D modeling, we re-constructed the primary olfactory center—the antennal lobe of A. dissimilis. In the antennal lobes 68.8 ± 3.1 male glomeruli and 70.8 ± 1.0 female glomeruli were identified with obvious sexual dimorphism. In particular, male adults of A. dissimilis contain a macroglomerular complex (MGC) that consists of three subunits, while the female lobe has four relatively enlarged glomeruli at the entrance of the antennal nerve. Glomeruli were later clustered with deviation and variance, and referring to reported olfactory related receptor family genes in seven different moth species, we found that glomerular counts of these insects are better related to the sum of odorant receptor and ionotropic receptor numbers, suggesting olfactory receptors and ionotropic receptors may both involved in olfaction of Noctuidae moths.